Immobilization of invertase on functionalized mesoporous silica and properties of the immobilized biocatalyst - Prabhune, Asmita Ashutosh; Sulabha, Karandikar; Archana, Pundle; Shilpa, Deshpande; Sanjeevani, Pardhy (Research Journal of Biotechnology, 2007)
Invertase, which catalyses the hydrolysis of sucrose, is one of the simplest commercial carbohydrases and is used for the production of invert syrup (mixture of glucose and fructose). Fructose is the sweetest natural sugar having beneficial medicinal effects and is emerging as an alternative sweetener to sucrose in the pharmaceutical industry. beta fructofuranosidase (E C 3.2.1.26) purified from Kluyveromyces marxianus NCYC 2675, a thermotolerant yeast, was immobilized on functionalized mesoporous silica SBA- 15. Attempts were made to immobilize invertase on functionalized silicalite and cross linked with glutaraldehyde so as to obtain a highly active and stable immobilized enzyme preparation suitable for commercial exploitation. Cross linked enzyme silica complex as well as enzyme silica complex showed very good temperature and pH stability. Extrudates of the mesoporous silica also showed similar results. Bound enzyme showed excellent stability to repeated use and retained 90% of its initial activity after ten cycles of reuse in batch mode.
Keywords: beta fructofuranosidase; extrudates; functionalized mesoporous silica; Invert syrup; invertase; SBA-15

Gellan Gum a novel polysaccharide matrix for immobilization of thermo-tolerant yeast cells with invertase activity: factorial design and rheological studies - Sulabha, Karandikar; Asmita, Prabhune (Research Journal of Biotechnology, 2012)
The microbial extracellular polysaccharide gellan gum has been explored for its application in whole cell immobilization. Preliminary evaluation of the physicochemical properties of gellan gum in the presence of monovalent cation tetramethyl ammonium chloride (TMACl) was carried out. Gellan gum immobilized cells demonstrated better rheological properties than gellan gum. Attempts have been made to reveal the evaluation of gellan gum as a matrix to immobilize a thermotolerant yeast Kluyveromyces marxianus NCYC 2675. A 3(2) factorial design was used to study the simultaneous effect of two variables. The effect of the polymer concentration and TMACl concentration on various dependent variables like gelling temperature, mean particle size and enzyme activity of the yeast cells was studied. A statistical model with a significant interaction term was obtained to predict the results. Further, optimized immobilized system was evaluated with significant storage stability at 10 C and enhanced reusability with maximum conversion of > 90 % when crosslinked with glutaraldehyde.
Keywords: Gellan gum; Glutaraldehyde; Immobilization; invertase; Rheology; yeast cells